The potential of trigona honey as a hemoglobin booster and immunomodulator in pregnant women with iron deficiency anemia - Ricca Afrida; Winda Nurmayani; Susilia Idyawati; Hawari Jannati; Raudatul Jannah (Institute of Computer Science (IOCS), 2026)
Background: Iron deficiency anemia in pregnancy constitutes a significant public health issue, as it elevates the likelihood of adverse pregnancy outcomes, including pregnancy complications. In West Lombok, the prevalence of anemia among pregnant women was reported to reach 18.6%. Despite government efforts through iron supplementation programs, challenges remain, including low adherence and limited bioavailability. Therefore, alternative natural supplements are needed. Trigona honey contains micronutrients and bioactive compounds with hematopoietic and immunomodulatory properties, making it a potential natural agent to improve hemoglobin levels and immune function. Objective: To examine the impact of Trigona honey supplementation on the hemoglobin levels of pregnant women with IDA. Methods: This true experimental research employed a pretest–posttest control group design and was carried out within the service area of the Jembatan Kembar Community Health Center. Thirty pregnant women were recruited using purposive sampling and divided into two groups: intervention (Trigona honey + iron) and control (iron only), each with 15 participants. Data were collected using questionnaires and Touch GCHB tests to measure hemoglobin levels. Statistical analyses were performed using paired and independent t-tests with a significance thresholdof p < 0.05. Results: Hemoglobin levels increased significantly in both groups; however, the intervention group demonstrated a more substantial improvement (mean = 2.89; p = 0.000) compared to the control group (mean = 0.65; p = 0.010). Conclusion: Trigona honey significantly enhanced hemoglobin levels compared to iron supplementation alone. It may serve as a promising non-pharmacological complementary therapy for preventing and managing iron deficiency anemia in pregnant women.